Principles of marketing - Randall, Geoffrey (Scott, Foresman/Little, Brown Higher Education, 2001)
This is the second edition of Randall's concise introductory text for general marketing courses, combining academic rigour with an accessible writing style. While providing a comprehensive overview of 'classical' marketing, the book also covers 'new' marketing, including the shift from transactions to relationships, one-to-one marketing and mass customisation, changes in the role and organization of the marketing function, marketing accountability and marketing metrics. With new chapters on e-commerce and branding, there is also additional material on marketing ethics/social responsibility, knowledge management and technical developments, environmental marketing, and a focus on financial marketing in the services marketing chapter